How to stir up FDI spillovers: Evidence from a large meta-analysis - Tomáš Havránek; Zuzana Iršová (Charles University in Prague, Institute of Economic Studies (IES), 2011)
The voluminous empirical research on horizontal productivity spillovers from foreign investors to domestic firms has yielded mixed results. In this paper, we collect 1,205 estimates of horizontal spillovers from the literature and examine which factors influence spillover magnitude. To identify the most important determinants of spillovers among 43 collected variables, we employ Bayesian model averaging. Our results suggest that horizontal spillovers are on average zero, but that their sign and magnitude depend systematically on the characteristics of the domestic economy and foreign investors. The most important determinants are the technology gap between domestic and foreign firms and the ownership structure in investment projects. Foreign investors who form joint ventures with domestic firms and who come from countries with a modest technology edge create the largest benefits for the domestic economy.
Keywords: C83; F23; O12; 330; Bayesian model averaging; Foreign direct investment; Productivity spillovers; Determinants; Meta-analysis